Exploring the Lived Social and Academic Experiences of Foreign-born Students: A Phenomenological Perspective - Selvitopu , Abdullah (Journal of International Students, 2020)
The purpose of this study is to provide a better understanding of the experiences of FBSs studying at a Turkish public university. The study attempted to provide useful findings for student services, faculties, policy makers, and other stakeholders to effectively address the needs, interests, and aspirations of FBSs, thereby helping them better adapt to school and community life in Turkey. The researcher collected the data in the winter of 2019 by utilizing an open-ended interview protocol with a snowball sampling of seven FBSs. Three themes emerged from the students’ spoken words: first days’ experience, balancing period through social experiences, and the lived academic experiences. Findings from this study suggest that FBSs have lived many positive and negative social and academic experiences. For most, negative experiences were transformed into positive ones with various facilitators that brought FBSs personal growth and better adaptation.